DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR UMKM KE ASEAN PADA PERIODE 2014 - 2019 - Kresnaufal Sudono, (2021)
MSMEs play an essential role and contribute to a country's export operations since they have an influence on economic growth and the welfare of its citizens, such as in Indonesia. MSMEs are a key component in each country's economic growth, particularly Indonesia's, in the ASEAN member countries. Indonesia has made several work to promote MSME exports to ASEAN in order to improve the competitiveness of Indonesian MSME products in the ASEAN market. The goal of this research is to assess how Indonesia's efforts to raise MSME exports to ASEAN have performed. This study takes a qualitative approach to data gathering and analysis, and it uses qualitative research methodologies. As primary and secondary data sources, interviews and literature were used to gather information. The framework for this research is economic diplomacy. Until the finding of the study shows that Indonesia has good and linked collaboration between the government and the private sector, business players, and interested parties in ASEAN to promote MSME exports to ASEAN.